Implementation Review of Indonesia’s Measured Fishing Policy (PIT) Supporting Sustainable Tuna Fishery in Banda Aceh - Agustina, Imelda; Rahmah, Alvi; Aprilla, Ratna Mutia; Mizan, Muhammad Khairul; Desmiyanti; Fuah, Ricky Winrison; Pandang, Ivonda Vicana (International Journal of Marine Engineering Innovation and Research, 2026)
The Indonesian Government has implemented the Measured Fishing Policy (PIT) through Government Regulation No. 11 of 2023 as an effort toward sustainable fisheries management. This policy regulates measured fishing according to fish resource potential within each Fisheries Management Area of the Republic of Indonesia (WPPNRI). The PIT policy has been applied in several regions, including Banda Aceh City, yet faces challenges such as limited port infrastructure, low local fishers’ awareness, and a lack of empirical data on its impacts on fishing productivity and welfare. This study aims to analyze changes in the productivity and income of tuna, skipjack, and frigate tuna fishers before and after PIT implementation in Banda Aceh. A mixed-methods approach was employed, combining production and fishing effort data from the Kutaraja Ocean Fishing Port (PPS Kutaraja) with in-depth interviews with fishers and stakeholders. Results show that tuna production peaked in 2024 at 395.35 tons/year and was lowest in 2021 at 33,99 tons/year. Skipjack production reached 1.502,79 tons/year, while frigate tuna production was highest in 2024 and lowest in 2022 (75.15 tons/year). Income analysis revealed that purse seine fisher’s profits were influenced by vessel, engine, gear investments, and operational and maintenance costs. In conclusion, the PIT policy affects the dynamics of local fishers’ productivity and income, providing an empirical basis for strengthening sustainable fisheries policy at the local level.